Erratum to: Asymptotic flux compactifications and the swampland - Thomas W. Grimm; Chongchuo Li; Irene Valenzuela (Journal of High Energy Physics, 2021)
In the original paper a wrong affiliation has been assigned to author Chongchuo Li during the typesetting.